New Seaport Development-Prospects and Challenges: Perspectives from Apapa and Calabar Seaports, Nigeria - Adepoju Olusegun Onifade (Logistics)
Arising from the menace of city logistics problems in Lagos State with reference, in particular, to the Apapa and Tin Can Island seaport axis, the federal and state governments, in collaboration with private investors, seek to establish and/or develop some potential seaports to ease the burden of maritime logistics. Therefore, the objectives of this paper are to examine the prospects and challenges of the development of these proposed seaports and to analyze the efficiencies of the two selected seaports in order to determine the need for the required investment in seaport development. Descriptive analysis was used to examine the challenges of the selected seaports, while stochastic frontier analysis (SFA) was used to determine the efficiency of the selected seaports. The responses of the stakeholders and shipping companies to the various challenges were collected through a well-structured questionnaire, and the 2008–2017 cargo throughputs of the selected seaports were used as the secondary data for stochastic frontier analysis (SFA). It was discovered that the challenges associated with the Calabar Seaport were the draught level, cost of shipment, accessibility to industries, and condition of other modes of transport. From the stochastic frontier, the Lagos Apapa seaport is quite efficient, with an efficiency value of 0.9764921, while Calabar is slightly above average, with a mean efficiency value of 0.6086686. By implication, the congestion in the seaports in the Lagos seaport complex with the maximum level of efficiency creates the need for another seaport, which must be sited at a well-vetted location. In the case of the Calabar seaport, the efficiency level shows that the seaport is yet to be fully utilized. Hence, investment decisions regarding whether to build a new seaport or use dredging to upgrade the existing ones must be carefully analyzed, as the establishment of the proposed Ibom deep seaport may further affect the efficiency of the Calabar seaport(s). In conclusion, demand should be the driving force for port establishment: when a port cannot generate enough traffic, it may not yield returns on investment as expected.